Transcatheter mitral valve repair and replacement; current therapies and general evaluation of new approaches - Alsancak, Yakup; Gürbüz, Ahmet Seyfettin; Düzenli, Mehmet Akif (Journal of Surgery and Medicine, 2017)
There have been a revolution in catheter based therapies for structural valvular heart diseases in last decade and many incredible improvements in the percutaneous treatment of mitral and aortic valve diseases. The use of transcatheter mitral valve repair has gained widespread acceptance in worldwide. More than 50.000 patients have been treated with percutaneous edge-to-edge repair system or annuloplasty systems. Although the most experience has been obtained with MitraClip®, using of percutaneous direct and indirect annuloplasty devices have been on the forefront in recent years. In addition, the percutaneous mitral valve replacement, like the transcathater aortic valve replacement (TAVI), will also be mentioned more in the near future.